Saberes e práticas tradicionais sobre recursos faunísticos e cultura alimentar na comunidade quilombola do Jacarequara, município de Santa Luzia do Pará, Amazônia Oriental - AVIZ, Manoel Fagno (Universidade Federal do Pará, 2022)
This dissertation goals to describe and analyze the knowledge and practices involved with faunal resources in the Quilombola Community of Jacarequara, in the municipality of Santa Luzia do Pará, Northeast of Pará state, Eastern Amazon. From an ethnozoological approach, the principal aim of this research was to understand the role of faunal resources in food culture and, in ensuring food security for the families observed. Participant observation, semi-structured interviews, open interviews and free listing were the main methodological tools used in data collection during the fieldwork carried out in 2020. The socioeconomic profile described shows a community made up of families dependent on self-production of food and on income transfer programs for the subsistence of the domestic group. The interviews and observations evidenced an immense diversity of animals present in the local ecological knowledge, included in five types of uses: food, medicinal, ritualistic, artisanal and pet or domestic creation. In addition, the data obtained revealed the very rich ethnozoological knowledge existing in the community, with details of habitats, trophic ecology, ethology and reproductive cycle of the species of interest. Such knowledge proved essential in the design and choices of hunting and fishing strategies. Animal extractives (hunting and fishing) proved to be a fundamental part of the community's daily life, where both practitioners and non-practitioners of these techniques are involved. The faunal resources are important elements in the community's food culture, evidenced by the existing food preferences and rejections, both in the way of preparation and in the way of consumption, as well as in the choice of the animal, also affecting the food restrictions represented in the food taboos system, which it shows itself as a regulator of consumption of certain species. We realized that environmental characteristics are directly linked to food choices, therefore environmental impacts in the region would have a great influence on the community's food culture, which could affect the food security of families. In conclusion, faunal socio-biodiversity plays a fundamental role in ensuring food and nutrition security and the food culture of the investigated quilombola community.